Efficacy and safety of pirfenidone in patients with second-degree burns: a proof-of-concept randomized controlled trial - Mecott, Gabriel A.; González Cantú, Iván; Dorsey Treviño, Edgar Gerardo; Matta Yee Chig, Daniel; Saucedo Cárdenas, Odila; Montes de Oca Luna, Roberto; Pérez Porras, Sergio; García Pérez, Mauricio M. (Wolters Kluwer Health, 2020)
OBJECTIVE: Several studies suggest that pirfenidone may have a potential off-label use for wound healing. However, the effectiveness of this medication in patients with burns remains uncertain. Accordingly, investigators sought to assess wound re-epithelialization in patients with second-degree burns after adding pirfenidone to usual care. DESIGN AND SETTING: Single-center pilot, proof-of-concept, single-blind randomized controlled trial. PATIENTS AND INTERVENTION: Eight patients with second-degree burns were treated with occlusive hydrocolloid dressings and were randomly allocated to receive either no additional treatment or pirfenidone. OUTCOME MEASURES: The primary outcome of the study was to evaluate wound healing between groups based on the thickness of the re epithelialized epidermis at day 7. Secondary outcomes were to qualitatively assess the development of fibrotic tissue in the dermis, anomalies in the basal membrane, and the development of collagen fibers by histologic analysis. Liver and renal functions were measured daily to assess the overall safety of oral pirfenidone. MAIN RESULTS: Patients treated with pirfenidone showed a remarkable improvement in wound re-epithelialization at day 7 (148.98 ± 13.64 vs 119.27 ± 15.55 μm; P = .029; 95% confidence interval, 4.14-55.29). Histologic evaluations showed less wound fibrosis in the pirfenidone group. CONCLUSIONS: A decrease in wound healing time by enhancing wound re-epithelialization was observed with pirfenidone. Larger clinical trials are needed to reach more reliable conclusions.